A2 Noradrenergic Lesions Prevent Renal Sympathoinhibition Induced by Hypernatremia in Rats - Pedrino, Gustavo Rodrigues; Freiria-Oliveira, Andre Henrique [UNESP]; Almeida Colombari, Debora Simoes [UNESP]; Rosa, Daniel Alves; Cravo, Sergio Luiz (Public Library Science, 2012)
Renal vasodilation and sympathoinhibition are recognized responses induced by hypernatremia, but the central neural pathways underlying such responses are not yet entirely understood. Several findings suggest that A2 noradrenergic neurons, which are found in the nucleus of the solitary tract (NTS), play a role in the pathways that contribute to body fluid homeostasis and cardiovascular regulation. The purpose of this study was to determine the effects of selective lesions of A2 neurons on the renal vasodilation and sympathoinhibition induced by hypertonic saline (HS) infusion. Male Wistar rats (280-350 g) received an injection into the NTS of anti-dopamine-beta-hydroxylase-saporin (A2 lesion; 6.3 ng in 60 nl; n = 6) or free saporin (sham; 1.3 ng in 60 nl; n = 7). Two weeks later, the rats were anesthetized (urethane 1.2 g.kg(-1) b.wt., i.v.) and the blood pressure, renal blood flow (RBF), renal vascular conductance (RVC) and renal sympathetic nerve activity (RSNA) were recorded. In sham rats, the HS infusion (3 M NaCl, 1.8 ml.kg(-1) b.wt., i.v.) induced transient hypertension (peak at 10 min after HS; 9 +/- 2.7 mmHg) and increases in the RBF and RVC (141 +/- 7.9% and 140 +/- 7.9% of baseline at 60 min after HS, respectively). HS infusion also decreased the RSNA (-45 +/- 5.0% at 10 min after HS) throughout the experimental period. In the A2-lesioned rats, the HS infusion induced transient hypertension (6 +/- 1.4 mmHg at 10 min after HS), as well as increased RBF and RVC (133 +/- 5.2% and 134 +/- 6.9% of baseline at 60 min after HS, respectively). However, in these rats, the HS failed to reduce the RSNA (115 +/- 3.1% at 10 min after HS). The extent of the catecholaminergic lesions was confirmed by immunocytochemistry. These results suggest that A2 noradrenergic neurons are components of the neural pathways regulating the composition of the extracellular fluid compartment and are selectively involved in hypernatremia-induced sympathoinhibition.